Poly(vinylpyrrolidinone)-Iron Magnetic Nanocomposites as Sorbents for Effective Oil Removal from Water - Shikh Mohd Shahrul Nizan Shikh Zahari; Nordin, NFNM; Kamarudin, MS; Mus'ab Sahrim; Mahat, MM; Azman, HH; Junid, R; Endot, NA (Amer Inst Physics, 2024)
Indexed by WOS/SCOPUS